PENGARUH MEDIA AUDIO VISUAL TERHADAP PASING BAWAH BOLA VOLI SISWA KELAS 10 SMA NEGERI 2 BENGKALIS - Yulia Purnamasari; Agus Sulastio; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine the level of influence of audio-visual media on the ability of passing down in class X SMA Negeri 2 Bengkalis in learning volleyball. The type of research used in this study was a quasi-experimental research with a quantitative descriptive approach. In this study, there was only treatment and there was a measure of success and also the absence of a control group. Based on the results of the research and discussion that the author has described, it can be concluded from the results of data analysis that it can be seen that the results of the posttest assessment of the passing ability of students in class X SMA Negeri 2 Bengkalis, for the "very good" category as many as 4 students or 19.05 %; "good" category as many as 11 students or 52.38%; the "medium" category as many as 4 students or 19.05%; "less" category as many as 2 students or 9.52%; and the category "very less" as many as 0 students or 0%, and this is also evidenced by the results of the t-test which shows that |t count| > t table is 9.293 > 2.086 which means that the initial hypothesis is accepted. Thus, it has been proven that the audio-visual approach in learning the underpassing ability of students in class X SMA Negeri 2 Bengkalis which was carried out 3 times, was able to improve student learning outcomes in learning the ability of passing down and also the magnitude of the increase in the ability of passing down can be seen from the difference in values. the average is 10.04, with a percentage increase of 42.52%.Key Words: Audio Visual Media, Under Passing Volleyball